Christaller, toujours vivant ! - Arnaud Banos; Diego Moreno; Cyril Pivano; Patrick Taillandier (Cybergeo, 2011)
This paper explores, with an agent-based model called « LivingChristaller, Christaller’s Central Places Model. Focusing on two distinct populations (consumers and producers), it restraints itself to the main hypothesis enunciated by Walter Christaller.